Analysis of association of socs5 gene polymorphism with allergic bronchial asthma and the level of its control - I. I. Cherkаshinа; A. B. Аveryanov; S. Yu. Nikulinа; V. N. Mаksimov (Туберкулез и болезни лёгких)
The objective: to analyze the frequency of genotypes and alleles of the rs6737848 polymorphism of the socs5 gene in patients with allergic bronchial asthma (BA) and to assess the association of this polymorphism with different levels of control over this disease.Subjects and methods. 179 people of the Caucasian race were the subjects of the study, and they all had the confirmed diagnosis of allergic asthma. The diagnosis, severity, and level of disease control were assessed in accordance with the GINA recommendations. The comparison group included apparently healthy individuals (n = 217).Results. The study of rs6737848 of the socs5 gene revealed statistically significant differences in the frequencies of genotypes and alleles in the group of patients with allergic asthma versus the group of healthy individuals. Among patients with allergic asthma, the frequency of the CC genotype and C allele was the highest. Carriers of the CG genotype and G allele prevailed among healthy individuals versus allergic asthma patients. Analysis of frequency distribution of genotypes and alleles of the rs6737848 polymorphism of the socs5 gene showed statistically significant predominance of the CC genotype and C allele in the sample of patients with allergic asthma that was fully or partially controlled.Conclusion. In women, the CC genotype and allele C of the socs5 gene can be considered as a genetic risk factor for the development of allergic asthma and a prognostic marker of controlled and partially controlled course of the disease. The CG genotype and G allele of the socs5 gene have a conditionally protective effect on the development of allergic asthma.